1979
DOI: 10.1136/sti.55.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Chlamydia trachomatis in acute salpingitis.

Abstract: SUMMARY Recent isolation studies have shown Chlamydia trachomatis to be an important aetiological agent in acute salpingitis in women. The present serological study indicates that C. trachomatis is the probable aetiological agent in two-thirds of 143 women with pelvic inflammatory disease (PID). In general, high levels of chlamydial antibody were found in sera and fluids aspirated from the pouch of Douglas and such antibody titres were shown to correlate with the severity of clinically graded tubal inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 11 publications
5
38
0
Order By: Relevance
“…The anti-chlamydial IgM seropositivity of 60% among the primary infertility group, highlighted a significant correlation between the prevalence of the antichlamydial antibodies and the tubal factor infertility which was secondary to acute salpingitis. These findings were consistent with other reports which were made by Treharne (73%) [13], Bhujwala (60%) [14] and Ghinsberg (43%) [15].…”
Section: Discussionsupporting
confidence: 83%
“…The anti-chlamydial IgM seropositivity of 60% among the primary infertility group, highlighted a significant correlation between the prevalence of the antichlamydial antibodies and the tubal factor infertility which was secondary to acute salpingitis. These findings were consistent with other reports which were made by Treharne (73%) [13], Bhujwala (60%) [14] and Ghinsberg (43%) [15].…”
Section: Discussionsupporting
confidence: 83%
“…Note that among the cases, a high proportion of the titers that would normally be considered positive (1:32 and above) are at particularly high levels. This has been observed repeatedly in similar studies of TFI (11,15,16,30,31), and PID (10,18). In other words, women at higher risk of reproductive damage are more likely to be CT antibody positive, and are more likely to have particularly high titers than antibody-positive controls.…”
supporting
confidence: 53%
“…The major studies of reproductive outcomes in women with PID (5-7) have been restricted to the small proportion of PID (8) that is diagnosed in hospital. In the 1980s and 1990s large numbers of serological case-control studies were carried out, comparing serum antibody levels in women with PID, EP or infertility, with controls (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These studies invariably showed strong associations between detection of CT antibodies and reproductive damage, but it was difficult to draw quantitative conclusions from them, partly because of confounding between CT and other pathogens also implicated in reproductive morbidity (20), and partly because of the poor, and imprecisely known, sensitivity and specificity of the assays used (21,22).…”
mentioning
confidence: 99%
“…Information has accumulated about the association of chlamydial infection and pelvic inflammatory disease (PID).1-3 Treharne et 4 (containing >100 inclusion bodies) on culture, only one (5%) was in the same category on direct examination. 14 (70%) were in category 3, four (20%) in category 2, and one (15%) in category 1 on direct examination.…”
Section: Introductionmentioning
confidence: 99%